Enzyme‐Based Glucose Sensor: From Invasive to Wearable Device. Issue 8 (15th January 2018) - Lee, Hyunjae; Hong, Yongseok Joseph; Baik, Seungmin; Hyeon, Taeghwan; Kim, Dae‐Hyeong
Abstract: Blood glucose concentration is a key indicator of patients' health, particularly for symptoms associated with diabetes mellitus. Because of the large number of diabetic patients, many approaches for glucose measurement have been studied to enable continuous and accurate glucose level monitoring. Among them, electrochemical analysis is prominent because it is simple and quantitative. This technology has been incorporated into commercialized and research‐level devices from simple test strips to wearable devices and implantable systems. Although directly monitoring blood glucose assures accurate information, the invasive needle‐pinching step to collect blood often results in patients (particularly young patients) being reluctant to adopt the process. An implantable glucose sensor may avoid the burden of repeated blood collections, but it is quite invasive and requires periodic replacement of the sensor owing to biofouling and its short lifetime. Therefore, noninvasive methods to estimate blood glucose levels from tears, saliva, interstitial fluid (ISF), and sweat are currently being studied. This review discusses the evolution of enzyme‐based electrochemical glucose sensors, including materials, device structures, fabrication processes, and system engineering. Furthermore, invasive and noninvasive blood glucose monitoring methods using various biofluids or blood are described, highlighting the recent progress in the development of enzyme‐based glucose sensors and their integrated systems. Abstract : Over the past decades, the electrochemical glucose sensors for diabetes care have improved tremendously, which enable a convenient tracking of blood glucose levels continuously. Here, the basic principles and recent progress in enzyme‐based electrochemical glucose sensors are reviewed, as well as their application to noninvasive blood glucose monitoring methods and to the conventional invasive methods.